2000
DOI: 10.1063/1.533321
|View full text |Cite
|
Sign up to set email alerts
|

Schrödinger operators in the twentieth century

Abstract: This paper reviews the past fifty years of work on spectral theory and related issues in nonrelativistic quantum mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 227 publications
0
91
0
2
Order By: Relevance
“…The continuity in the case of the presence of magnetic vector potentials was stated in [54] as an open problem; only several years ago Simon's results were extended in [7,8] to magnetic Schrödinger operators on domains in Euclidean space with vector and scalar potentials of Kato's type. In the both cases, the proof used certain probablistic technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuity in the case of the presence of magnetic vector potentials was stated in [54] as an open problem; only several years ago Simon's results were extended in [7,8] to magnetic Schrödinger operators on domains in Euclidean space with vector and scalar potentials of Kato's type. In the both cases, the proof used certain probablistic technique.…”
Section: Introductionmentioning
confidence: 99%
“…A huge literature is dedicated to the study of properties of H A,U in its dependence on A and U , see the recent reviews [48,54,55]. An essential feature of the quantummechanical operators in comparision to the differential operator theory is admitting singular potentials [19], although the operator itself preserves some properties like regularity of solutions [29].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of self-adjointness results for one-dimensional operators can be found in N. Dunford and J. Schwartz [25]. About the multidimensional case (for operators on R n ) the reader may consult M. Reed [26], and also review papers by H. Kalf, U.-W Schminke, J. Walter and R. Wüst [43], H. Kalf [41] and B. Simon [83]. We tried not to repeat these sources unless this was relevant for the main text of our paper.…”
Section: Appendix C Stummel and Kato Classesmentioning
confidence: 99%
“…However, the presence of a non-trivial singular continuous part of ρ for some potentials was only guessed. More attention to the subject was attracted when Simon [28] asked the following question.…”
Section: Then the Support Of The (Possible) Singular Part Of ρ Has Hamentioning
confidence: 99%